2006
DOI: 10.1007/s11095-006-9173-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–temporal VEGF and PDGF Delivery Patterns Blood Vessel Formation and Maturation

Abstract: Spatially localizing and temporally controlling growth factor presentation for angiogenesis can create spatially organized tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
252
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(273 citation statements)
references
References 24 publications
9
252
2
3
Order By: Relevance
“…Two strategies that hold promise for improving tendonbone healing include gene transfer of PDGF-BB into tenocytes that can then be delivered to the repair site [23,30] and the design of new biodegradable material carriers for local and sustained delivery of cytokines at the healing enthesis [6,7,21]. Further studies, in larger animal models, where the healing environment is slower, are needed to optimize the delivery of this potentially useful growth factor to possibly augment structural healing and reduce the retear rate after rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
“…Two strategies that hold promise for improving tendonbone healing include gene transfer of PDGF-BB into tenocytes that can then be delivered to the repair site [23,30] and the design of new biodegradable material carriers for local and sustained delivery of cytokines at the healing enthesis [6,7,21]. Further studies, in larger animal models, where the healing environment is slower, are needed to optimize the delivery of this potentially useful growth factor to possibly augment structural healing and reduce the retear rate after rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that this method significantly enhances tissue regeneration compared with the controlled release of single biological cues. [293][294][295] For example, one group recently reported enhanced pluripotent cellular differentiation, ALP activity, and matrix mineralization through sequential delivering BMP-2 and IGF-I through a novel layered biodegradable polymer scaffold. 222 Another group demonstrated enhanced osteogenic differentiation in vitro through sequential administration of BMP-2 and -7 via polymer degradation.…”
Section: Delivery Of Multiple Bioactive Moleculesmentioning
confidence: 99%
“…Many recent strategies have concentrated on enhancing vessel stabilization in vitro, such as encapsulating different growth factors within the scaffold, or use of different mural cell types 22, 23, 24. In this study, we present application of oscillatory strain as a simple means of enhancing vessel stabilization and morphogenesis within engineered tissues.…”
Section: Discussionmentioning
confidence: 99%